Reality and Business Policy Decisions - Barton, Richard F. (Academy of Management Journal, 1966)
The article examines assumed reality with respect to business policy decisions. The author argues that managers create the facts, truth and reality on which they base their decisions and when the decision is made, facts and truth remain elusive and unmeasurable. The article discusses reality, decision making, uncertainty and efficiency, conflict and values, business policy decisions, strategies, and reality creation. The author argues that when making decisions, decision makers have assumed the conditions under which they act and have balanced the consequences by creating a reality within which to act.